Information physics : physics-information and quantum analogies for complex systems modeling - Svitek, Miroslav, 1969- (Academic Press, 2021)
"[P]resents a new theory of complex systems presented by using the analogy with various aspects of physics--electronics, magnetic circuits, and quantum mechanics. The key idea presented by Dr. Miroslav Svitek is the recognition of information flow and information content as the main quantities in informatics as, for example, electrical current and voltage are used in electrical engineering. With respect to this idea, the known mathematical instruments of electrical/magnetic circuit modeling can be applied to the modeling of complex information systems. Such an approach leads to better definition of an event's source that includes both an information content (quality of the information source) and an information flow (how the information source is distributed). Another result is the clear separation between an information source and an information recipient. The recipient sometimes is not able to process the transmitted information and it uses only its part. The presented model can consider such situations. ... [A]lso explains the quantum approach to system theory that can be understood as an extension of classical system models. The main idea is that in many complex systems there are a lot of incomplete pieces of overlapping information that must be composed together to find the best consistent model for the while. The incomplete information can be understood as a set of nonexclusive observers' results--each of them represents the reality through its limited capabilities. Because they are nonexclusive, each observer registers different pictures of the reality. Quantum models with information pieces can be interconnected in serial, parallel, and feedback ordering. They can also be time-varying with a lot of interesting features such as entanglement, emergency, or self-organization. Dr. Svitek presents the ways in which such mathematical instruments can be applied to many fields, including the human sciences"--Page 4 of cover.